DYNAMICS OF COLLABORATIVE GOVERNANCE IN COMMUNITY-BASED INTEGRATED CHILDREN PROTECTION (PATBM) DURING THE COVID-19 PANDEMIC IN INDONESIA - Bintari, Antik; Soleh, Iman (CosmoGov: Jurnal Ilmu Pemerintahan, 2021)
Child protection is basically the responsibility of all parties, especially children are the key to the future of a nation. Therefore, the government does not work alone but requires synergy with other parties such as the private sector, universities, mass media, and the community where the children live and work. The governance model that involves multi-stakeholders to make public decisions is known as collaborative governance.Collaborative governance is one of the new strategies of government that involves various stakeholders in a forum to make joint decisions that aim to solve problems that exist in society.One of the collaborative networks in child protection initiated by the Ministry of Womens Empowerment and Child Protection (Kemen PPPA) since 2016 is known as the Community-Based Integrated Child Protection (PATBM) movement. PATBM during the COVID-19 pandemic was part of efforts to fulfill childrens rights, especially in terms of preventing and responding to cases of violence against children that occurred at PATBM locationsgb777